MOTIVATION IN LANGUAGE LEARNING: A NEEDS-ORIENTED APPROACH (Modern education and development, 2025)
Motivation plays a vital role in second and foreign language acquisition. It influences not only the learners’ desire to begin learning a language but also their persistence and overall success in achieving proficiency. This article explores the importance of motivation in language learning with a particular focus on needs-oriented approaches. Drawing upon key theories and classroom-based practices, the paper examines how identifying and responding to students’ specific needs can significantly enhance motivation and learning outcomes.